Effects of Phytic Acid Extracted From Rice Bran on Azoxymethane-Induced Colon Carcinogenesis in Rats - Saad, Norazalina (2008)
This research is carried out to study the potential of phytic acid extracted from rice bran in the suppression of colon carcinogenesis in rats. In the optimization of phytic acid extraction, results showed 5% H2S04 in pH 0.6 and 30 minutes of extraction time gave the highest amount of phytic acid. In animal study, 72 male Sprague-Dawley rats were divided into 6 groups with 12 rats in each group; Group 1: ADM alone, Group 2: AOM + 0.2% (w/v) Commercial Phytic Acid (CPA), G roup 3: ADM + 0.5% (w/v) Commercial Phytic Acid (CPA), Group 4: ADM + 0.2% (w/v) Extract P hytic Acid (EPA) , G roup 5: AOM + 0.5% (w/v) Extract Phytic Acid (EPA). Rats received two subcutaneous injections of azoxymethane (ADM) in saline at (15mg/kg bodyweight)" over a 2-weeks period to induce colon cancer. The treatments were given in two different concentrations of phytic acid; 0.2% (w/v) and 0.5% (w/v) during post initiation of carcinogenesis phase via drinking water. The colons of the animals were analyzed for detection and quantification of aberrant crypt foci (ACF) after 8 weeks of treatment. The finding showed treatment with 0.2% (w/v) EPA gave the greatest reduction in the formation of ACF. In addition, phytic acid significantly suppressed the number of ACF in the distal, middle and proximal colon as compared to AOM a lone (p<0.05). For the histological classification of ACF, treatment with 0.5% (w/v) CPA had the highest percentage (71%) of non-dysplastic ACF followed by treatment with 0.2% (w/v) EPA (61%). After 20 weeks of treatment, colons of the rats were excised and analyzed for tumor incidence. Results showed that administration of phytic acid reduced the incidence and multiplicity of total tumors and adenocarcinomas even though there were no significant differences between groups. For the immunohistochemical analyses, proliferating cell using Ki-67 and modulating of B-catenin and COX-2 expression were assessed as those have been shown to play a role in tumor progression . In Ki-67, there was a statistically significance difference in lowering the proliferating index between treatment groups as compared to AOM alone (p<0.05). For B-catenin a nd COX-2 expression, there was a significant difference between g roups as (p=O.OOO) and (p=0.030). In the correlation test, the results showed that there was a significant positive correlation (p=0.010) between proliferation of Ki67 and COX-2 expression. A positive linear relationship was found between total Ki67 and Bcatenin but these relationships were not statistically significant. Total B-catenin had a significant positive linear relationship with total COX-2 (p=0.044). As a conclusion, this study found the potential value of phytic acid extracted from rice bran in reducing colon cancer risk in rats. Besides identification of cancer reduction strategies based on dietary modification including looking at natural sources that may have anticancer properties, an alternative compound from local sources has been developed. Therefore, rice bran that is normally discarded as by-product of rice production will increase in value due to phytic acid potential as a nutraceutical compound in the prevention of colon cancer progression.